Pengaruh Total Asset Turnover, Debt To Equity Ratio, dan Net Profit Margin terhadap Return Saham Perusahaan Ritel Bei 2021-2024 - Rahma Maripatu Saripah; Heidi Siddiqa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study was conducted to evaluate the influence of Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) in predicting stock return fluctuations. The study focuses on retail sector issuers listed on the Indonesian Stock Exchange (IDX) between 2021 and 2024. Through the application of panel data regression analysis, the study determined that the Common Effects Model (CEM) is the most appropriate estimation method. This decision was made based on a series of tests including the Chow Test and the Lagrange Multiplier. Although classical assumption testing showed symptoms of heteroscedasticity, this problem was addressed using the EGLS (cross-sector weighting) Panel method to ensure the validity of the estimates. Based on partial testing, it is found that TATO and NPM variables have a positive and significant contribution to stock returns, while DER is found to have no significant effect. Collectively, all independent variables had a significant effect, with the Adjusted R-Square value reaching 27.80%. This indicates that for investors in the retail sector, profitability and operational efficiency are important indicators in making investment decisions.